A 4 year retrospective study of facial dog bite injuries in patients reported to pediatric emergency, BPKIHS, Nepal. - Dali, Mamta; Koirala, Bandana; Shrestha, Sneha; Birajee, Gajendra (Birat Journal of Health Sciences, 2023)
Introduction: Dog bites facial injuries are a significant health care problem and their sequelae ranges from minor to fatal injuries. Objectives: To determine the incidence of facial dog bite injuries and to assess the outcome as well as presentation of facial injuries among the children reported to the pediatric emergency, BPKIHS, Nepal. Methodology: A study was conducted where the clinical records of children with facial dog bite injuries reported from 2015 to 2018, were assessed and analyzed.A proforma was designed to extract relevant clinical data from the case records. Information such as age, gender of the victims, anatomical site of the injury, interval between injury and presentation to the hospital, nature of injuries,profile(stray or pet)and immunization status the of dog ,outcome and complications were extracted. Results: The incidence of facial dog bite injuries has significantly increasedpointing maleschool going children injured predominantly(70%).Seventeen(81%) victims had presented within 24 hrs of injury whereas two(9.5%) patients had reported after 24 hours and 72 hours of the injury. Nineteen patients were treated on the same dayunder local anesthesia, one under general anesthesia where thorough wound lavage with meticulous reapproximation followed by suturing was done. Full recovery was evident in eighteen (86%) cases with primary wound closure whereas two (14%) patients had undergone healing with secondary intention. Conclusion: There is an increase in incidence of dog bite facial injuries among children in our tertiary health care centre. Satisfactory healing outcomes were achieved with a thorough wound lavage and primary closure of non-infected wounds under appropriate rabies prophylaxis and proper antibiotic regimen.